Medical and Folklore Images during Pandemics: A Study of Edo Period Epidemic Visual Culture - Yi ZENG; Yongzhi XIAO; Yang YANG (Chinese Medicine and Culture)
Abstract. Edo-period historical records and documents preserved a substantial number of images, many of which are related to epidemic outbreaks. Through systematic collation and categorical analysis, this study uses the chronological and thematic characteristics of these images as a framework to examine the response mechanisms of the Japanese government and public during infectious disease pandemics in the Edo period, as well as the multidimensional impacts of epidemics on social economy, culture, and customs. Illustrations of smallpox in medical texts reveal the developmental trajectory of Japan’s traditional medical knowledge system, while drawings in essays and diaries reflect public fear and non-medical cognitive patterns during cholera outbreaks. Epidemic-themed paintings not only document cholera treatment protocols by the government and medical professionals, as well as grassroots prevention and treatment practices for measles, but also vividly depict social dynamics during crises. Images related to epidemics in advertising reflect the prosperity of the pharmaceutical industry in the Edo period, while depictions in folding screens, ukiyozoushi and the occupational illustrations demonstrate societal customs for epidemic response. Collectively, the Edo-period epidemic crises profoundly shaped Japan’s medical system, economic structure, cultural forms, folk traditions, and public psychology, prompting the government, medical professionals, and civilians to develop distinct era-specific social coping mechanisms.